El estudio de la lexicografía en el Perú: hacia una historiografía de la lexicografía peruana - Huisa Téllez, José Carlos (Mercurio Peruano, 2013)
This article presents several steps that should be undertaken in future studies of Peruvian lexicography. A particular focus is set on the role of discourse traditions in Hispano-American lexicography and various fields of future research in Hispano-American historiography.
Keywords: Hispano-American lexicography, historiography, metalexicography